Christian Science : a sourcebook of contemporary materials - Christian Science Publishing Society (Boston, Mass. : Christian Science Pub. Society, 1990)
Conveniently compiled published documents accurately reflect Christian Science beliefs and practices. The book contains basic facts about Christian Science, emphasizing its theology, and topics range from perspectives on the Bible to the practice of spiritual healing. - Publisher.
Four overviews -- Christian Science and the Bible -- Theological dialogue -- Healing as a Christian experience -- Christian healing in the modern world -- The church and society -- Historical perspective on Mary Naker Eddy -- Towards a scientific Christianity.
Includes bibliographical references (pages 319-321) and index.
Keywords: Eddy, Mary Baker, -- 1821-1910.; Christian Science; Medicine -- Religious aspects; Mental healing; Religion and Medicine; Mental Healing; Christian Science; Christian Science